Thermosensitive Molecular, Colloidal, and Bulk Interactions Using a Simple Surfactant. (10th September 2012) - Kodger, Thomas E.; Sprakel, Joris
Abstract Efficient use of (nano)particle self‐assembly for creating nanostructured materials requires sensitive control over the interactions between building blocks. Here, a very simple method for rendering the interactions between almost any hydrophobic nano‐ and microparticles thermoswitchable is described and this attraction is characterized using colloid probe atomic force microscopy (CP‐AFM). In a single‐step synthesis, a thermoresponsive surfactant is prepared that through physical adsorption generates a thermosensitive brush on hydrophobic surfaces. These surface layers can reversibly trigger gelation and crystallization of nano‐ and microparticles, and at the same time can be used to destabilize emulsions on demand. The method requires no chemical surface modification yet is universal, reproducible, and fully reversible.